Generalized moment representations and multipoint padé approximants - Holub, A. P. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We establish conditions for the maximal dissipativity of one class of densely-defined closed linear operators in a Hilbert space. The results obtained are applied to the investigation of some special differential boundary operators.